2014
DOI: 10.1038/ncomms5537
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex reactivity underlies trait vulnerability to chronic social defeat stress

Abstract: Psychological stress contributes to the onset and exacerbation of nearly all neuropsychiatric disorders. Individual differences in stress-regulatory circuits can therefore dramatically affect vulnerability to these illnesses. Here we identify neural circuit mechanisms underlying individual differences in vulnerability to stress using a murine model of chronic social defeat stress. In chronically stressed mice, we find that the degree of prefrontal cortex (PFC) control of amygdala activity predicts stress-susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 49 publications
6
108
1
7
Order By: Relevance
“…In addition to the NAc, several other brain regions have also been implicated in susceptibility to SDS, including the medial frontal cortex (mFC) (28,29) and the amygdala (Amyg) (30). Interestingly, Tph2KI mice have previously been reported to exhibit aberrant connectivity between the mFC and the Amyg (31).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the NAc, several other brain regions have also been implicated in susceptibility to SDS, including the medial frontal cortex (mFC) (28,29) and the amygdala (Amyg) (30). Interestingly, Tph2KI mice have previously been reported to exhibit aberrant connectivity between the mFC and the Amyg (31).…”
Section: Resultsmentioning
confidence: 99%
“…Anatomical 3D volumetric images were converted to MINC format, and were registered iteratively: (i) to a reference image using 6 degrees of freedom (df) transform, (ii) by 12 df affine transformation between each pair of individual images, and (iii) with 3 consecutive non-linear transformations between each pair of images, using MICe-build-model and ANTS (Lerch et al, 2008). Region of interest analysis was performed using a set of ROIs derived from the Allen mouse brain atlas (http://www.mouse.brain-map.org) adapted to MRI space.…”
Section: Data Processingmentioning
confidence: 99%
“…Therefore, it will be important to build on the present evidence for increased between-network FC involving the amygdala in CPS mice in terms of understanding the changes in the excitation-inhibition between these networks. Interestingly, in CSD mice, an electrophysiology study also demonstrated increased coherence between the neuronal firing signals obtained from PFC and amygdala (Kumar et al, 2014). In human FC studies, the amygdala has been studied mainly in the affective network, depression-related changes in which remain to be investigated (Dutta et al, 2014).…”
Section: Increases In Within-and Between-network Functional Connectivmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work by the Dzirasa laboratory has also shown that naturally occurring differences in corticolimbic synchrony correlates with trait vulnerability to CSDS, with greater phase locking between the PFC and amygdala predicting increased vulnerability. 163 Interestingly, as mentioned above, animal and human studies have shown that 5-HT is a major regulator of vmPFC-amygdala coupling and reducing 5-HT using genetic mouse models of 5-HT deficiency or pharmacological treatments has been shown to favor cortico-amygdala hypersynchrony and enhance vulnerability to social defeat (Figure 5). 164 …”
Section: Social-experience-induced Structural and Functional Plasticimentioning
confidence: 96%